DEVELOPMENT OF ISLAMIC BANKING IN THE REPUBLIC OF UZBEKISTAN: INSTITUTIONAL PREREQUISITES AND LIMITATIONS (World Economics and Finance Bulletin, 2026)
The article examines the opportunities and limitations of introducing Islamic banking in the Republic of Uzbekistan. Based on an analysis of international practice and the ongoing reforms of the country’s financial sector, the study explores the institutional, legal, and economic conditions for the development of Islamic finance. The potential impact of Islamic banks on expanding access to finance, attracting foreign investment, and diversifying sources of capital is assessed. The paper substantiates the necessity of establishing an effective regulatory framework and a Sharia supervisory system to ensure the sustainable development of this segment.
Keywords: Islamic banking; Sharia-compliant finance; financial system of Uzbekistan